Cultural diversity drives innovation: empowering teams for success. Issue 3 (22nd September 2020) - Jones, Graham; Chirino Chace, Bernardita; Wright, Justin
Abstract : Purpose: Though there is broad agreement on the beneficial impact of diversity in management and leadership roles, much of the innovative capacity of an organization is realized at the unit level in working teams. Recent research points to cultural diversity having an especially significant impact on innovation team performance. The reports also highlight the need for the optimal team operating principles to derive maximum benefit. To prepare such innovation teams for success, it is valuable to understand the dynamics of team diversity at the project level and the underlying barriers and opportunities presented. Design/methodology/approach: This paper reviews the literature and case studies on cultural inputs to ideation and innovation, assessing team diversity through readily available instruments and the deployment of the science of team science (SciTS) principles in innovation teams. Findings: The key learnings include the importance of establishing communication standards, SciTS principles, team assessment of thinking styles and the utility of cultural awareness instruments. Practical implications: Diversity provides a creative advantage for innovation teams. However, team dynamics play an important role in maximizing these advantages, and cross-cultural competence of team members is required. Deployment of appropriate assessment tools and team methodologies enhances the likelihood of successful outcomes including in remote team settings. Originality/value: Literature from diverse functional areas is summarized including the science of team science, organizational management, diversity and inclusion methodologies and ethnocultural dynamics. It provides pointers for the optimal formation and operating principles with highly culturally diverse teams.